0908 Avoidant Coping As A Mediator Of The Sleep-Pain Relationship In Mid- To Late-life. (27th April 2018) - Ravyts, S; Dzierzewski, J; Schreiber, D; Grah, S; Perez, E; Raldiris, T
Abstract: Introduction: Sleep has reliably been shown to predict future pain, however, the mechanisms through which sleep contributes to increased pain are not yet fully understood. Poor sleep is known to impair emotion regulation and promote maladaptive coping. In addition, maladaptive coping patterns are known to increase pain. Yet, relatively little research has examined the role of coping on the relationship between sleep and pain. This study explored whether avoidant coping acts as a mediator of the sleep-pain pathway. Methods: Archival data from the Midlife in the United States-III study (MIDUS-III), Project 1 was used. Participants included of 938 adults (mean age= 64.50 years, 58.3% female). Sleep disturbance was conceptualized as the mean frequency of self-reported difficulty with sleep onset latency, wake after sleep onset, early morning awakening, and daytime sleepiness, each measured on a 6-point Likert scale. In addition, participants reported average total sleep time (TST) on both weekdays and weekends. Pain was conceptualized as the average amount pain interfered with general activity, mood, relationships, and enjoyment of life, each on a 11-point Likert scale. Finally, avoidant coping was assessed using the COPE Inventory. Results: After controlling for selective covariates, mediational analyses revealed an indirect effect of sleep disturbance on pain interference via avoidant coping (β =.06, CI: .02, .11). Specifically, greater sleep disturbance predicted increased levels of avoidant coping (β = .21, p <.001), which, in turn, predicted higher levels of pain interference (β =.27, p =.001). In addition, TST also had a significant indirect effect on pain interference via avoidant coping (β = -.001, CI: -.002, -.0001). Conclusion: Findings suggest that avoidant coping may partially explain the sleep-pain relationship. Researchers and clinicians would therefore benefit from routinely assessing sleep and coping among adults with pain. In addition, either intervening on sleep or promoting more adaptive coping skills may be beneficial in reducing pain interference. Support (If Any): This work was supported by the National Institute on Aging (1K23AG049955, PI: Dzierzewski).